2013
DOI: 10.4194/1303-2712-v13_2_21
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although fish is a significant source of protein, they are currently affected by rapid industrialization and mechanized agricultural activities, resulting in increased concentrations of heavy metals in fishes. Concentrations of heavy metals, namely, Cd, Cu, Mn, and Zn, were estimated in the muscle, liver, and gills of two commercially important marine fishes, namely, Arius thalassinus and Johnius belangeri. The fish samples were collected from Kapar and Mersing, which are the west and east coastal waters of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…A comparison between available fish species metal concentration data and the present study is shown in Table 7. It is evident that the range of concentration of metal elements in other parts of the world are lower than that of the presently studied data [52][53][54][55][56]. On the other hand, the obtained data is comparable to similar studies in the neighboring regions [57,58].…”
Section: Trace Metal Concentrationsupporting
confidence: 72%
See 1 more Smart Citation
“…A comparison between available fish species metal concentration data and the present study is shown in Table 7. It is evident that the range of concentration of metal elements in other parts of the world are lower than that of the presently studied data [52][53][54][55][56]. On the other hand, the obtained data is comparable to similar studies in the neighboring regions [57,58].…”
Section: Trace Metal Concentrationsupporting
confidence: 72%
“…The maximum allowed concentration of Pb in fish is 0.21 mgkg −1 DW set by JECFA [51], whereas in our study we found that the fish Sillaginopsis panijus, Sardinella longiceps, Trichiurus lepturus, and all the crustacean species contained Pb concentrations exceeding the limit. According to FAO/WHO, the acceptable limit of Cd for human consumption is 0.20 mgkg −1 [52]. Among the fish species, Sardinella longiceps, Konosirus punctatus, and among the crustacean species Portunus sanguinolentus, Scylla serrata, and Penaeus semisulcatus exceeded this limit.…”
Section: Trace Metal Concentrationmentioning
confidence: 99%
“…This result agrees with the data described in Qureshi and Saksena (1980). As stated in (Nussey et al, 1995;Bashir et al, 2013;Sağlam et al, 2014), the copper has significant toxic effects on fish even at low concentrations. In addition, the partial LC 10 values of copper sulfate were higher when compared with those of LC 50 values in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out on metal pollution in different species of edible fish. Predominantly, fish toxicological and environmental studies have prompted interest in the determination of toxic elements in seafood [7–10]. According to the Codex Committee for Food Additives and Contaminants, dietary intakes of heavy metals with high public concern need to be monitored on a regular basis and rapidly updated to identify recent dietary intakes of heavy metals in developing countries.…”
Section: Introductionmentioning
confidence: 99%